The sage in Jewish society of late antiquity - Kalmin, Richard Lee (Routledge, 1999)
"The Sage in Jewish Society of Late Antiquity explores the social position of rabbis in Palestinian (Roman) and Babylonian (Persian) society from the period of the fall of the Temple in 70 CE to late antiquity. The author argues that ancient rabbinic sources depict comparable differences between Palestinian and Babylonian rabbinic relationships with non-rabbis. Palestinian sages interacted closely with non-rabbis, in part because of their relatively insecure place in society, whereas Babylonian sages occupied a stronger place in society and could therefore afford to keep their distance from non-rabbis. Richard Kalmin also discusses the historicity of rabbinic portrayals and places rabbinic scriptural comments in a historical context. He argues that these interpretations were motivated not only by a desire to explicate the Biblical text but also by social, cultural, religious, polemical and apologetic concerns."--Jacket